A cross-sectional survey of knowledge and attitude towards HIV/AIDS patients among nursing students in teaching hospital - Othman, Hamidah; Mohd Ali, Noor Azizah (The Malaysia Journal of Nursing, 2017)
HIV/AIDS is a matter of concern and has become a pandemic disease that threatens the world population. It has remained one of the priorities in global public health challenges. Caring for people with HIV/AIDS requires clinical expertise as well as high-quality skills for health care providers. The purpose of the study was to examine knowledge and attitude on HIV/AIDS patients among nursing students. A cross-sectional study was conducted in Public University at Wast Cost Malaysia. The 126 respondents of nursing students agreed to participate in the study using a self-administered questionnaire that was designed and modified after reading and referring to articles, books, and journals. The results of the research revealed that nursing students, in general, have a satisfactory knowledge (mean score 30.71), but had a moderate attitude toward HIV/AIDS patient with total mean score 2.34. Most of the students (89.3%) get the knowledge regarding HIV/AIDS through the internet. The majority of the students knew that blood transfusion (99.4%) and sharing needles/syringe (99%) were the higher sources HIV/AIDS modes of transmission. Most of the students agreed that peoples with HIV/AIDS should be treated in society with support from the community (97.0%). Although the knowledge level of nursing students seems to be satisfactory, but they still showed the moderate attitude towards HIV/AIDS patients. Thus, structured education programmes should be conducted by nursing faculty to ensure that nursing students gain the necessary accurate knowledge and an appropriate attitude towards the care of HIV/AIDS patients.